2021
DOI: 10.3389/fnut.2021.705763
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic Effects of Lactobacillus fermentum ZJUIDS06 and Lactobacillus plantarum ZY08 on Hypercholesteremic Golden Hamsters

Abstract: Hypercholesteremia or high cholesterol is one of the important factors leading to atherosclerosis and other cardiovascular diseases. The application of probiotics with cholesterol-lowering characteristics has become increasingly popular over the past decade due to their contribution to human health. This study aimed to evaluate the probiotic effects of Lactobacillus fermentum ZJUIDS06 and Lactobacillus plantarum ZY08 on hyperlipidemic golden hamsters. A hyperlipidemic model was established through a high chole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 76 publications
2
22
0
Order By: Relevance
“…As a probiotic, J‐15 mainly plays a role in regulating intestinal flora affected by kidney stone formation and helped restore the intestinal flora. This is pretty consistent with previous investigation on the changes in intestinal or fecal abundance of genus Lactobacillus after the administration of Lactobacillus strains in other disease models, 52,53 which might be due to the strain specificity, dosage, different animal models, and intestinal segments 54–56 . Our previous study on the microbial community composition of different intestinal segments after L .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As a probiotic, J‐15 mainly plays a role in regulating intestinal flora affected by kidney stone formation and helped restore the intestinal flora. This is pretty consistent with previous investigation on the changes in intestinal or fecal abundance of genus Lactobacillus after the administration of Lactobacillus strains in other disease models, 52,53 which might be due to the strain specificity, dosage, different animal models, and intestinal segments 54–56 . Our previous study on the microbial community composition of different intestinal segments after L .…”
Section: Discussionsupporting
confidence: 92%
“…This is pretty consistent with previous investigation on the changes in intestinal or fecal abundance of genus Lactobacillus after the administration of Lactobacillus strains in other disease models, 52,53 which might be due to the strain specificity, dosage, different animal models, and intestinal segments. [54][55][56] Our previous study on the microbial community composition of different intestinal segments after L. plantarum administration revealed that the amount of genus Lactobacillus varied widely among intestinal segments, 57 with the higher levels in the ileum and less in the cecum and colon. It suggests that L. plantarum significantly regulates the intestinal microflora of the ileum, rather than the cecum and colon.…”
Section: Discussionmentioning
confidence: 99%
“…Each strain of the Lab4 consortium possesses gene sequences encoding phosphate acetyltransferase and acetate kinase that are involved in the generation of acetate ( 31 ): acetate is recognised as an anti-inflammatory SCFA known to inhibit the expression of IL-6 by colon cells ( 32 ). The recent study of Yang et al showed that administration of Lactobacillus fermentum ZJUIDS06 increased levels of acetic, propionic and butyric acid in the colons of hypercholesterolemic hamsters whilst significantly reducing plasma cholesterol levels ( 33 ). SCFA are known to have pleiotropic effects on the host and there is growing evidence supporting beneficial effects on cholesterol metabolism ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, genes that are not statistically different are indicated by a cross. In this analysis, Package “corrplot” was used to visualize the results ( 29 , 30 ).…”
Section: Methodsmentioning
confidence: 99%